Needs analysis for the development of website-based interactive infographic modules in Arabic grammar learning - Abdul Hamid, Mohd Fauzi; Sahrir, Muhammad Sabri; Ab. Halim, Zulazhan; Yahaya, Mohd Firdaus; Nasir, Mohd Shahrizal; Sha'ari, Shaferul Hafes; Amiruddin, Ahmad Zaki (Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia, 2024)
The use of technology in learning Arabic grammar can help students understand easier and with less difficulties. Infographics are one of the alternatives of today's technology that aim to make learning information simple, interesting and easy to understand. This study focuses on students' views on the need to develop web-based interactive infographic modules in learning Arabic grammar. This study uses the Design and Development Research approach. Questionnaire instruments were used to obtain analysis data related to the use of learning materials, learning approach issues, the tendency to utilise innovation and the needs of using interactive infographics. A total of 205 students from Bachelor of Arabic Studies, UniSZA who had taken Ibn Aqil's Syntax Text Study course were made to be respondents thats answer the questionnaire. Data were analysed using the Statistical Package for Social Science (SPSS) software to obtain the mean and standard deviation. The data from the answered questionnaire shows that students collectively agreed that the development of an interactive infographic module should be developed. Interactive infographic content can attract students to understand complex lesson contents.